Pengaruh Pricing Strategy, Promotion Strategy Dan Brand Equity Differences Terhadap Marketing Position Pt.Garuda Indonesia (Persero), Tbk Branch Office Manado (Rute Penerbangan Manado-Denpasar) - Simboh, Kevin F.; Tampi, Johny R. E.; Tamengkel, Lucky F. (Sam Ratulangi University, 2018)
In an increasingly sophisticated era, the lifestyles of peoples are increasingly advanced and also increase the rate of oneâ€™s mobility. Nowdays, the companies is required to be able to act, act quickly and accurately in facing competition in this world. Various problem come when many low-cost airlines come to the surface by offering and enabling their power to attract consumers, this problem making Garuda Indonesia not have a top position Marketing Position on Manado-Denpasar Route. This study discusses about the influences of Pricing Strategy, Promotion Strategy and Brand Equity Differences against the Marketing Position PT.Garuda Indonesia Branch Office Manado (Manado - Denpasar Route ). Marketing is one of the most important activities int the business world. In the curent business. In Marketing activites there are 4 Marketing `Mixes which are Product, Price, Place and Promotion. conditions, marketing is a driver to increase sales, so that purpose of companyâ€™s are achived. Â The method used in this study is quantitative by using questionnaires as a tool to gather information from respondents. Respondents were determined based on whether their used the service of Garuda Indonesia in 2 times, so this study can be said to be using a probability sampling method with a sample random sampling retrieval techniques. This study uses multiple lineaar regressio n analysis, 3 indpendent variable and 1 dependent variable. The survey was conducted by taking a sample of 50 passengers of Garuda Indonesia. This study aims to find out whether Pricing Strategy, Promotion Strategy and Brand Equity Differences affect to Marketing Position of the company and to describe what is the most important factor according to passengers perception to bring this company as Top lead er at Marketing Poosition board. The results obtained in this study indicate that there is a significant influence between Pricing Strategy, Promotion Strategy and Brand Equity Differences against to Marketing Position. The results of this study also show that Promotion strategies are the most important factor in its influence on Marketing Position. Keywords: Pricing startegy , Promotion strategy, Brand equity, Marketing Position.